2020
DOI: 10.2217/pgs-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Telomere Length Between Patients with Bipolar Disorder and Controls are Influenced by Lithium Treatment

Abstract: Aim: To assess the role of lithium treatment in the relationship between bipolar disorder (BD) and leukocyte telomere length (LTL). Materials & methods: We compared LTL between 131 patients with BD, with or without a history of lithium treatment, and 336 controls. We tested the association between genetically determined LTL and BD in two large genome-wide association datasets. Results: Patients with BD with a history lithium treatment showed longer LTL compared with never-treated patients (p = 0.015), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…A recent study found that bipolar disorder patients who had never been treated with lithium had shorter telomeres than healthy controls, while patients treated with lithium had longer telomeres than the never treated patients, although not compared to healthy controls. 17 Our finding that antidepressant medication use was associated with reduced telomere length in individuals with depression confirms a preliminary study showing that antidepressant use (n=40) was associated with shorter telomeres, independent of depression diagnosis and current depression severity. 40 Although previous research suggested that age-related decline in telomere length was greater in individuals with chronic stress or comorbidities, 41 we observed similar association between telomere length and age in individuals with mental disorders and the control group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A recent study found that bipolar disorder patients who had never been treated with lithium had shorter telomeres than healthy controls, while patients treated with lithium had longer telomeres than the never treated patients, although not compared to healthy controls. 17 Our finding that antidepressant medication use was associated with reduced telomere length in individuals with depression confirms a preliminary study showing that antidepressant use (n=40) was associated with shorter telomeres, independent of depression diagnosis and current depression severity. 40 Although previous research suggested that age-related decline in telomere length was greater in individuals with chronic stress or comorbidities, 41 we observed similar association between telomere length and age in individuals with mental disorders and the control group.…”
Section: Discussionsupporting
confidence: 88%
“…16 Bipolar disorder patients not exposed to lithium had shorter telomeres than patients who had been treated with lithium. 17 Most previous studies have had limited sample sizes and few studies have included cross-disorder comparisons within the same database. There has also been little exploration of associations between telomere length and genetic risk for mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated TL in patients with MDD and different results have been found, some of which showed that TL is shorter in patients than in non-psychiatric controls [66][67][68][69][70]. Similar findings have been reported in BD [67,[71][72][73][74], and different studies showed that treatment with the mood stabilizer lithium correlated with longer LTL [75][76][77]. Fewer studies investigated differences in TL between responders and non-responders to antidepressant treatment.…”
Section: Introductionmentioning
confidence: 82%
“…In the analysis of GWAS data, we observed no significant enrichment between genetic variants associated with LTL and variants nominally associated with response to ECT. While LTL is a highly heritable trait, and shorter genetically predicted TL has been associated with increased risk of some disorders, such as coronary artery disease and other cardiovascular disorders [59,85], previous studies aiming to assess the presence of an enrichment between genetic variants associated with LTL and psychiatric phenotypes mostly yielded negative results [77,86,87].…”
Section: Discussionmentioning
confidence: 99%
“…Powell et al ( 122 ) reported longer TL in buccal smears from lithium-treated BD patients compared to patients not on lithium treatment while Coutts et al ( 123 ) found an association between chronic lithium treatment and longer whole blood TL in BD patients ( 122 , 123 ). Most recently, Pisanu et al ( 124 ) reported that BD patients with a history of lithium treatment had longer leukocyte TL compared to those who never had been treated with lithium and similar TL compared to controls ( 124 ). In the only prospective clinical study on lithium’s effect of TL thus far, Köse Çinar ( 125 ) found that manic BD patients had shorter TL than healthy controls and that TL was significantly increased at remission after treatment with lithium and antipsychotics ( 125 ).…”
Section: Telomere Maintenancementioning
confidence: 99%